Trophallaxis and reproductive conflicts in social bees - Contrera, F. A. L.; Imperatriz-Fonseca, V. L.; Koedam, D. [UNESP] (Birkhauser Verlag Ag, 2010)
In the eusocial Hymenoptera, reproductive division of labour is a key aspect of colony organisation. In most of its species, workers are sterile and are unable to reproduce, while the queen monopolises reproduction. When workers are able to reproduce, a conflict with the queen or with other workers over male production is predicted. Because this reproduction may involve costs for the colony, the potential conflict over male parentage gives rise to important questions, such as what are the proximate mechanisms that allow a queen to control the reproductive potential of its workers, and which factors make some workers fertile and others not. In the groups where it occurs, an important mechanism for the regulation of reproduction is trophallaxis (the process of mutual feeding through regurgitation that occurs in several species of social insects). Trophallaxis gives dominant individuals a trophic advantage by taking nutrients from submissive individuals. In advanced eusocial species of bees, trophallaxis may also serve as an alternative hierarchical interaction in the absence of agonistic conflicts. In this way, trophallaxis not only represents an alternative path for hierarchical interactions, but it may be evolutionary linked to intracolonial conflict among workers.
Keywords: Food exchange; Nutrition; Halictidae; Apini; Meliponini